2003
DOI: 10.1161/01.hyp.0000084853.47326.f2
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase–Derived Superoxide Augments Endothelin-1–Induced Venoconstriction in Mineralocorticoid Hypertension

Abstract: Abstract-Deoxycorticosterone acetate (DOCA)-salt hypertension is characterized by low renin/angiotensin but increased arterial superoxide levels. We have recently reported that the arterial endothelin-1 (ET-1) level is increased, resulting in NADPH oxidase activation and superoxide generation. However, the effect of ET-1 on venous superoxide production and its relation to venoconstriction are unknown. The present study tested the hypotheses that ET-1 stimulates venous NADPH oxidase and superoxide via its ET A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 37 publications
4
69
1
1
Order By: Relevance
“…It has been demonstrated that, in addition to the interactions of O 2 Ϫ ⅐ and NO in endothelium-dependent vasodilation, the redox signaling mechanism is involved in the constrictor response of arterial smooth muscle to a variety of agonists such as angiotensin II (12,15,17), arginine vasopressin (25), norepinephrine (44), thromboxane A 2 (46,58), and endothelin (6,25). Moreover, endogenous O 2 Ϫ ⅐ has been reported to participate in the vascular myogenic response and the vascular reaction to electrical stimulation (14,19,36,41).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that, in addition to the interactions of O 2 Ϫ ⅐ and NO in endothelium-dependent vasodilation, the redox signaling mechanism is involved in the constrictor response of arterial smooth muscle to a variety of agonists such as angiotensin II (12,15,17), arginine vasopressin (25), norepinephrine (44), thromboxane A 2 (46,58), and endothelin (6,25). Moreover, endogenous O 2 Ϫ ⅐ has been reported to participate in the vascular myogenic response and the vascular reaction to electrical stimulation (14,19,36,41).…”
Section: Discussionmentioning
confidence: 99%
“…51 Similarly, chronic ET-1 infusion is associated with Despite mixed results using the antioxidant tempol, there is clear evidence that ET stimulates superoxide production through an NADPH oxidase-dependent manner in DOCA-salt hypertensive rats. 55,56 Because ET A receptor blockade and superoxide scavenging can attenuate the hypertension associated with DOCA-salt treatment, it is reasonable to hypothesize that ETdependent hypertension could be inhibited by disruption of NADPH oxidase subunit assembly with the inhibitor, apocynin. Elmarakby et al have recently demonstrated that apocynin inhibits the increase in oxidative stress associated with chronic ET-1 infusion, yet the resulting hypertension was unaffected.…”
Section: Et B Receptors In Hypertensionmentioning
confidence: 99%
“…55,56 Because ET A receptor blockade and superoxide scavenging can attenuate the hypertension associated with DOCA-salt treatment, it is reasonable to hypothesize that ETdependent hypertension could be inhibited by disruption of NADPH oxidase subunit assembly with the inhibitor, apocynin. Elmarakby et al have recently demonstrated that apocynin inhibits the increase in oxidative stress associated with chronic ET-1 infusion, yet the resulting hypertension was unaffected.…”
Section: Et B Receptors In Hypertensionmentioning
confidence: 99%
“…) and reactive oxygen species (ROS) in VSM (Sedeek et al, 2003;Touyz et al, 2004;Li et al, 2003;Galle et al, 2000;Wedgwood et al, 2001). In cultured rat aortic VSM cells, ET-1 dose dependently (10 -8 to 10 -6 mol·l -1 ) increased the formation of O 2 .- (Sedeek et al, 2003) and, in human gluteal VSM cells, similar results were noted (Touyz et al, 2004).…”
Section: -mentioning
confidence: 57%